2016
DOI: 10.1242/dev.130120
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal protein CP110 controls maturation of mother centriole during cilia biogenesis

Abstract: Defects in cilia centrosomal genes cause pleiotropic clinical phenotypes, collectively called ciliopathies. Cilia biogenesis is initiated by the interaction of positive and negative regulators. Centriolar coiled coil protein 110 (CP110) caps the distal end of the mother centriole and is known to act as a suppressor to control the timing of ciliogenesis. Here, we demonstrate that CP110 promotes cilia formation in vivo, in contrast to findings in cultured cells. Cp110−/− mice die shortly after birth owing to org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 58 publications
5
71
1
Order By: Relevance
“…CP110 is a key marker in ciliogenesis process (25,26). Our previous study demonstrated that the increased expression of CP110 in mucosa from patients with chronic rhino sinusitis (CRS) was associated to the poor ciliation (15).…”
Section: Discussionmentioning
confidence: 99%
“…CP110 is a key marker in ciliogenesis process (25,26). Our previous study demonstrated that the increased expression of CP110 in mucosa from patients with chronic rhino sinusitis (CRS) was associated to the poor ciliation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Tau tubulin kinase 2 (TTBK2) is required for cilia initiation and mutants lack all cilia and Hh-dependent ventral neural cell types (Goetz et al 2012). Embryos that lack CP110, a protein that localizes to the distal ends of mother centrioles, also have fewer cilia and mild defects in Hh signaling (Yadav et al, 2016). …”
Section: Centriole and Basal Body Proteins Are Also Required For Thementioning
confidence: 99%
“…Expansion of this ciliary vesicle gives rise to the ciliary membrane, which is assembled in parallel with the axoneme. Axoneme outgrowth is associated with removal from the distal mother centriole of CP110, a protein with both positive and negative roles in early ciliogenesis (Spektor et al 2007; Tsang et al 2008; Kobayashi et al 2011; Yadav et al 2016). Axoneme formation also involves the construction of the TZ and recruitment of intraflagellar transport (IFT) particles, the microtubule motor-driven complexes that mediate ciliary transport and assembly (Lu et al 2015).…”
Section: Transition Fibersmentioning
confidence: 99%